Anti-inflammatory and hepatoprotective effects of glycyrrhetinic acid on CCl4-induced damage in precision-cut liver slices from Jian carp (Cyprinus carpio var. jian) through inhibition of the nf-kƁ pathway. Issue 64 (May 2017) - Cao, Liping; Ding, Weidong; Jia, Rui; Du, Jingliang; Wang, Tao; Zhang, Chunyun; Gu, Zhengyan; Yin, Guojun
Abstract: In order to evaluate the antioxidant and anti-inflammatory effects of glycyrrhetinic acid (GA) on carbon tetrachloride (CCl4 )-induced damage in precision-cut liver slices (PCLS) from Jian carp ( Cyprinus carpio . Jian), an acute liver damage model was established in this study. The viability of PCLS, levels of anti-oxidases in liver homogenates, expression of inflammation-related genes including nuclear factor-κB ( nf-κB )/ c-rel, inducible nitric oxide synthase ( inos ), interleukin-1β ( il-1β ), interleukin-6 ( il-6 ) and interleukin-8 ( il-8 ), and protein levels of ( nf-κB )/ c-rel in liver tissues were measured. The results showed that pretreatment of PCLS with GA at 5 and 10 μg/mL for 6 h significantly inhibited the cytotoxicity of CCl4 . GA attenuated CCl4 -induced oxidative stress in PCLS through promoting the recovery of superoxide dismutase (SOD) and glutathione (GSH) levels, and inhibiting malondialdehyde (MDA) synthesis. In inflammatory response, GA at both 5 and 10 μg/mL significantly inhibited the increase in mRNA levels of inflammatory cytokines including nf-kƁ / c-rel, inos, il-1β, il-6 and il-8, and the protein level of Nf-kƁ/C-rel induced by CCl4 . Furthermore, treatment with pyrrolyl dithiocarbamate (PDTC, 4 μg/mL), an inhibitor of nuclear transcription factor nf-kB, significantly inhibited nf-kB levels, and transcription of downstream cytokines inos, il-1β, il-6 and il-8, also the viability of PCLS was significantly increased. These results indicated that GA suppressed inflammation and reduced cytotoxicity by inhibiting the nf-kƁ signaling pathway, and plays a role in liver protection. Highlights: GA could protect PCLS damaged by CCl4 . GA inhibited the cytotoxicity caused by CCl4 . GA regulates cytokine production via the nf-κB signaling pathway.